PENGARUH ORIENTASI KEWIRAUSAHAAN DAN MANAJEMEN KUALITAS TERHADAP KEUNGGULAN BERSAING USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) INDUSTRI PANGAN DI KOTA BENGKULU - Darius - (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2016)
SMEs as a driver of development potential of the area-based social economy. SMEs in the food industry, the city of Bengkulu who have an entrepreneurial orientation can develop their business activities and expand market share by producing a quality product that is able to survive in the competitive business world that is increasingly dynamic. This study aims to analyze and determine the effect of orientation entrepreneurship or quality management to competitive advantage SME food industry in the city of Bengkulu. This study used a survey approach to sampling methods using purposive sampling method with a total sample of 118 respondents and analyzed by simple linear regression. The results of this study are: orientation entrepreneurship influence the food industry the competitive advantage of SMEs in the city of Bengkulu and quality management influence the competitive advantage of SMEs in the food industry city of Bengkulu.  Keywords: orientation entrepreneurship, quality management, competitive advantage, SMEs food industry